TET3 regulates hematopoietic stem cell homeostasis during embryonic and adult hematopoiesis - Harmony C. Ketchum; Claudia Morganti; Chie Yanase; Blake Ebert; Keisuke Ito; Meelad M. Dawlaty (HemaSphere, 2025)
ABSTRACT The ten‐eleven translocation family of enzymes (TET1/2/3) promotes DNA demethylation and is essential for hematopoiesis. While the roles of TET1 and TET2 are well‐studied in hematopoiesis, the requirement of TET3 in embryonic and adult hematopoiesis is less investigated. In this study, by characterizing embryonic and adult hematopoiesis in Tie2+/cre; Tet3f/f mice, we have established a requirement for TET3 in regulating hematopoietic stem cells (HSCs; CD150+CD48–). We found that loss of TET3 in the fetal liver and adult bone marrow causes a reduction in the percent of long‐term HSCs (LT‐HSCs; CD150+CD48–CD34–). This was accompanied by reduced colony forming capacity of TET3‐deficient HSCs in vitro and reduced contribution of HSCs after a competitive bone marrow transplantation in vivo. TET3 deficiency increased DNA methylation at several cell cycle regulator genes leading to their down regulation. This is consistent with, and likely underpins, the reduced number of quiescent HSCs in TET3‐deficient bone marrow. These findings uncover a new role for TET3 in HSC homeostasis during embryonic and adult hematopoiesis.